Male and female labour force participation: the role of dynamic adjustments to changes in labour demand ; government policies and autonomous trends - Maarten C. M. Vendrik; Frank Cörvers (Institute for the Study of Labor (IZA), 2009)
This study investigates the extent and speed of dynamic adjustment of labour supply to changes in labour demand, government policies and autonomous trends. We estimate error-correction models (ECMs) for male and female participation rates in the Netherlands between 1969 and 2004. The results show significant short and long-run effects of labour demand as well as a negative autonomous trend for male participation. In contrast, we find no significant long-run labour-demand effects and a very strong positive autonomous trend for female participation. Including female and male participation as additional explanatory variables in the male and female ECMs, respectively, reveals significant substitution effects between female and male participation. For male participation the substitution effects from female participation account for the negative trend in the basic ECM, while for female participation the substitution effects from male participation counterbalance labour demand effects that are now significant. In addition, we find very significant breakpoints in male and female participation at 1994, which indicate the effects of exogenous participation-promoting policies by the Dutch governments after 1994. The adjustments of the participation rates to changes in labour demand, government policies and autonomous trends are moderately fast.
urn:nbn:de:101:1-20091009982
Keywords: J21; J20; E32; 330; Labour force participation; discouraged worker effect; business cycle effects; persistence; substitution effect; error-correction model; Frauenerwerbstätigkeit; Arbeitsangebot; Männer; Arbeitsnachfrage; Konjunktur; Faktorsubstitution; Frauenpolitik; Niederlande